Experiences installing Firepower Services on an ASA-5525 X technical enablement series - Lewis, Aaron (International Business Machine Corporation, 2016)
This IBM Redpaper describes a case study that involves software and hardware from Cisco Systems, Inc. Specifically, a Cisco FirePOWER module -- also known as a SourceFire (SFR) module -- was installed on a Cisco Adaptive Security Appliance (ASA). The case study reveals the steps, issues, and decision points of such an installation. The scope of this case study is as follows: FirePOWER 6.2.0 on an ASA 5525-X running code level 9.6.2 from the Command Line Interface (CLI). We do not discuss the ASDM installation method. This document addresses the needs of Network Administrators, Security Administrators, and other staff who install and manage Intrusion Prevention or Intrusion Detection systems (IPS / IDS). The reader should have a basic understanding of computer networking and be familiar with basic networking terms such as Interface, Access Control Lists (ACL), Domain Name Service (DNS), and Internet Protocol (IP) address.
"IBM Redpaper.". - Online resource; title from cover (viewed November 12, 2019)
Keywords: Cisco FirePOWER (Electronic resource); Computer security -- Management; Sécurité informatique; Gestion; Computer security; Management